Filth - Welsh, Irvine (Vintage, 1999)
James McAvoy stars as a corrupt, sociopathic Edinburgh cop in director Jon S. Baird's fast-paced black comedy, adapted from the novel by Irvine Welsh. Bored with his duties as a Detective Sergeant in the Edinburgh police force, Bruce Robertson (McAvoy) gorges himself on a mixture of cocaine, alcohol, sexually abusive relationships and endless junk food, whilst plotting to get one over on his colleagues in his quest for a promotion. But although he nurses hopes of getting back together with his ex-wife Carole (Shauna MacDonald), Bruce soon finds his life spiralling out of control, when his drug addiction and unchecked psychological issues combine to test his grip on reality and push him over the edge.